Morphology, post-embryonic development, and reproduction of Taphronota ferruginea (Fabricius, 1781) (Orthoptera: Pyrgomorphidae) - Sévilor Kekeunou; Alain Christel Wandji; Charly Oumarou Ngoute (Tropical Zoology, 2018)
Taphronota ferruginea (Orthoptera: Pyrgomorphidae) is a pest of crops and forest trees. In order to contribute to the search for better strategies of fighting against this pest, this study was aimed at describing some aspects of its biology and ecology. Different nymphal instars collected in Nkongoa were reared in cages at the laboratory on Voacanga africana (Stapf, 1894), under a range of temperature 21.18–25.67°C (averagely 23.13°C) and relative humidity of 64.14–83.7% (averagely 75.5%). The post-embryonic development passed through six nymphal instars after hatching. Developmental duration of the sixth nymphal instar was longer than that of the fifth instar, which was also longer than those of first to fourth instars. Survival to adulthood increased with initial nymphal instar reared. Sexual dimorphism was highlighted in adults and in nymph of fifth and sixth instars. Pterotheca, female valves, male subgenital plates, total body length, color, and number of antenna segments were useful characters in distinguishing between nymphal instars. Adult female averaged 42.57±6.29 days to start mating. Egg-laying occurred on average of 45.78±4.74 days after first mating. Each female laid a single ootheca and the number of eggs per ootheca was averagely 30.44±5.06.